FAKTOR – FAKTOR YANG MEMPENGARUHI KEJADIAN PRE EKLAMSIA DI PUSKESMAS PENANGGAL KABUPATEN LUMAJANG - Azizah, Durrotul; Rohmatin, Homsiatur; Farianingsih, Farianingsih (NHM PRESS, 2023)
Current health developments in Indonesia are still marked by the vulnerability of maternal and child health, especially where maternal and child mortality rates are still high. The high maternal mortality rate due to the uncontrolled development of preeclampsia contributes greatly to the high mortality rate. The incidence of preeclampsia in Indonesia alone is 128,273/year or around 5.3%. Based on data in Lumajang Regency in 2022 there will be 646 cases of pre-eclampsia. The purpose of this study was to determine the factors that influence the incidence of pre-eclampsia at the Penanggal Health Center. This study used a cross-sectional design with an analytic observational type. Data collection was carried out in May 2023 with a population of 305 respondents and a sample of 35 respondents who met the inclusion and exclusion criteria using a random sampling technique. Data processing includes coding, editing, and tabulating, then analyzed with SPSS Chi-Square test software with α 0.05. The results of the study after the Chi-Square test showed the age of the pregnant woman with a p-value of 0.027, the working status of the mother with a p-value of 0.020, the educational status with a p-value of 0.028, and the status of pregnant women with a p-value of 0.03. This shows that there is a relationship between the incidence of pre-eclampsia and the age of pregnant women, employment status, mother's education, and gravida status. It is hoped that this research can provide knowledge and insight to pregnant women about the incidence of pre-eclampsia. In addition, it can be used as a reference for future researchers and can develop research with the same title but with different methods.